Application of synchronized tandem welding to high-hardness armor steel - Bo Wook Seo; Young Cheol Jeong; Hwi Jun Son; Chang Jong Kim; Seok Kim; Young Tae Cho (Heliyon, 2024)
Several studies have been conducted to improve combat vehicle capabilities, such as the bulletproof performance of armor and fuel efficiency through weight reduction. Titanium alloys and ceramic materials are expensive and difficult to process; therefore, they can be applied only in specific locations. In addition, arc welding, which is relatively inexpensive compared with other welding processes, is widely used in industrial fields; however, because welding is often performed in multiple passes to join one part, the productivity is reduced. Therefore, in this study, mechanical properties were investigated according to production time and heat input by applying tandem pulse gas metal arc welding (GMAW) to increase productivity. The experimental data were obtained by varying the wire feeding speed. In addition, the current–voltage waveforms were measured, and the volume shift was analyzed by comparison with images captured using a high-speed camera. To analyze the mechanical properties of the tandem weld for the welding of high-hardness armor plates, the appearance (top bead and back bead), cross-section, hardness, tensile test, impact test, and spatter generation of the welded part were analyzed. The results show that all Tank-automotive and Armaments Command (TACOM) standards for the base material were met when the tandem wire feeding speed was 11 + 11 m/min, and the single-pass process increased production speed by a factor of more than 10. Tandem pulse GMAW is shown to be a viable option for improving productivity and maintaining high-quality welds for high-hardness materials.